Dynamic Voltage Restorer Application for Power Quality Improvement in Electrical Distribution System: An Overview - Omar, Rosli; Sulaiman , Marizan (Insipub, 2011)
Dynamic Voltage Restorer (DVR) is a custom power device that is used to improve voltage disturbances in electrical distribution system. The components of the DVR consist of voltage source inverter (VSI), injection transformers, passive filters and energy storage. The main function of the DVR is used to inject three phase voltage in series and in synchronism with the grid voltages in order to compensate voltage disturbances. The Development of (DVR) has been proposed by many researchers. This paper presents a review of the researches on the DVR application for power quality Improvement in electrical distribution network. The types of DVR control strategies and its configuration has been discussed and may assist the researchers in this area to develop and proposed their new idea in order to build the prototype and controller.